Proposal of LED-based linear lighting systems with low power consumption and high light distribution for laying hens - Granja Barros, Juliana de Souza (2020)
The commercial production of eggs demands artificial illumination for reproductive stimulation of birds. The lighting systems currently used have limitations when applied in aviaries and need improvements to enable energy savings and production optimization. This study presents three original contributions: (i) the proposal of a low-power linear lighting system, developed for the commercial production of eggs, and methodology for sizing of linear lighting; (ii) comparative analysis of the same with the conventional LED lamps for energy efficiency, illuminance distribution, depreciation and temperature emission; and (iii) use of geostatistical method for analysis of the vertical light distribution in aviary. Based on the results, the linear lighting system in flexible LED strips reduced energy consumption by 32% compared to LED lamps and improved light distribution in cages. The LED strips showed low depreciation rate of the luminous flux (approximately 2% in 1080 h of use in the aviary). High surface temperatures were observed in the LED lamps (79.2 degrees C basal region of the LED lamp vs. 26.0 degrees C LED strip), which can contribute to the increase of energy consumption by the ventilation systems of the aviaries, and impair the conditions of comfort heat of the birds. Thus, the LED strips developed in the present study offer greater energy efficiency and can be a viable alternative technology for aviaries.